2018
DOI: 10.1016/j.semarthrit.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic patterns and predictors of hydroxychloroquine nonadherence among Medicaid beneficiaries with systemic lupus erythematosus

Abstract: Among HCQ initiators with SLE, we observed poor adherence which declined for most over the first year of use. HCQ adherence is a dynamic behavior and further studies of associated predictors, outcomes, and interventions should reflect this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 44 publications
6
81
0
1
Order By: Relevance
“…In this report, we introduce the concept of HCQ blood level monitoring to reduce the chances of prescribed dosages being too high. Although both the mean and maximum blood levels predict risk, we believe mean blood levels provide a better measure than maximum levels in the assessment of risk due to the issues of patient nonadherence (30,37,38) and due to the variation we observed even when the patient was adherent. Correlation of HCQ blood levels with skin pigmentation (39) and gastrointestinal side effects has been reported (35).…”
Section: Discussionmentioning
confidence: 83%
“…In this report, we introduce the concept of HCQ blood level monitoring to reduce the chances of prescribed dosages being too high. Although both the mean and maximum blood levels predict risk, we believe mean blood levels provide a better measure than maximum levels in the assessment of risk due to the issues of patient nonadherence (30,37,38) and due to the variation we observed even when the patient was adherent. Correlation of HCQ blood levels with skin pigmentation (39) and gastrointestinal side effects has been reported (35).…”
Section: Discussionmentioning
confidence: 83%
“…We excluded all claims from Ohio because detailed medication dispensing data were not available, and we additionally excluded all individuals without drug dispensing data, including those who were hospitalized for the entire follow‐up period. We identified 2 cohorts of patients with SLE (≥2 International Classification of Diseases, Ninth Edition [ICD‐9] codes for SLE [710.0] for discharge diagnoses or physician claims ≥30 days apart) with either AZA or MMF dispensing within 365 days of an SLE code . We required ≥6 months of continuous enrollment without use of AZA or MMF prior to the date of initiation (index date).…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to medications for SLE varies from 20% to 80% depending on the population studied, the medication, and the method used to measure adherence (e.g., self‐reported surveys, blood levels, prescription refill data) . Higher rates of nonadherence have been observed among younger age groups, African American and Hispanic patients, and individuals with less education . Studies have varied as to whether polypharmacy and disease severity affect the risk for nonadherence.
Adherence to the 2 most frequently used immunosuppressive medications for systemic lupus erythematosus (SLE), azathioprine (AZA) and mycophenolate mofetil (MMF), is overall extremely poor during the first year of use among a national cohort of Medicaid beneficiaries with SLE. Adherence overall was slightly better to MMF compared to AZA; however, adherence to both medications declined significantly for nearly 80% of patients over the first year of use. While demographic factors including African American race, Hispanic ethnicity, and younger age were associated with higher odds of nonadherence among AZA initiators, they were significantly less strongly associated with nonadherence among MMF initiators.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, multiple studies have shown high levels of very poor adherence, generally ranging from 20% to 50% of patients 38,39,40,41,42 . Common reasons for poor adherence cited by patients include fear of adverse effects and lack of understanding of the benefits 32,43 .…”
Section: Rheumatologymentioning
confidence: 99%